Tradisi Reog Ponorogo di Desa Mrayan Sebagai Pengenalan Budaya untuk Generasi Muda - Aidah Mustikarani; Atiqa Sabardila (FBS Padang State University, 2023)
The purpose of this research is to; 1) Knowing the complaints experienced by Reog dancers in Mrayan Village, 2) Knowing the series of Reog performances in Mrayan Village, 3) Knowing the differences between Reog Ponorogo in the past and present. There are data collection methods carried out by researchers are interview and questionnaire techniques. The results of this study are; 1) Jathil dancers in Mrayan Village said that the complaints they often felt were pain and aches in the shoulders, calves, and wrists. For very severe or fatal injuries, dancers in Mrayan Village have never been found, 2) The series of Reog performances in Mrayan Village include remarks by the village head, the dancers pray together, start the show, and close, 3) Differences between Reog dancers in the past and now there is Jathil. Which in ancient times were played entirely by men but now they have changed to Jathil dancers played by women. Jathil dancers in the village of Mrayan no longer have male dancers because the youth there think